The Effect of Areca Nut Husk Compost and Urea Fertilizer on the Growth of Areca Nut (Areca catechu L.) Seedlings in Peat Soil Media - Mutaqin, Zaenal; Linda, Linda; Indrastuti, Erning; Solihin, Eso (Universitas 17 Agustus 1945 Samarinda, 2025)
The growth of areca nut (Areca catechu L.) seedlings in peat soil media often faces challenges due to the low nutrient content and less favorable chemical properties of the soil. This study aims to analyze the effect of applying areca nut husk compost and urea fertilizer on the growth of areca nut seedlings in peat soil media. The research was conducted using a factorial randomized complete block design (RCBD) with two factors. The first factor was the dosage of compost (K) with five levels: 0, 0.25, 0.50, 0.75, and 1 kg. The second factor was the dosage of urea fertilizer (N) with four levels: 0.0, 1.5, 3.0, and 4.5 g. The results showed no interaction between the application of areca nut husk compost and urea fertilizer on plant height, stem diameter, and the number of leaves. However, the independent effect of areca nut husk compost significantly influenced the increase in height, stem base diameter, and the number of leaves in areca nut seedlings. Urea fertilizer had a significant effect on the increase in plant height and stem base diameter but did not significantly affect the increase in the number of leaves. The best application dosage for areca nut husk compost was 1 kg, which resulted in the greatest increase in plant height, stem diameter, and the number of leaves. The best urea fertilizer dosage for plant height increase was 4.5 g, while a dosage of 3 g produced the best increase in stem base diameter.